Attendance taking using QR code - Tan, Desmond De Xuan (Nanyang Technological University, 2023)
This final year report presents the development and implementation of ‘NTU Attendance’, a Quick Response (QR) code-based attendance taking system that can be used in Nanyang Technological University (NTU). The system consists of two different Graphical User Interfaces (GUIs), a desktop application and a mobile application. The desktop application will be used by the professors to generate QR codes for lessons as well as being able to access the attendance of the students. The mobile application will be used by the students to scan the QR code as well as being able to keep track of their lessons. With this attendance taking system being implemented, it aims to reduce the time required for attendance taking as every student can scan the QR code after the professor projects the QR code on the screen. The report concludes with future works and recommendation of the ‘NTU Attendance’ system.